2022
DOI: 10.53391/mmnsa.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Bi-dimensional crime model based on anomalous diffusion with law enforcement effect

Abstract: Several models based on discrete and continuous fields have been proposed to comprehend residential criminal dynamics. This study introduces a two-dimensional model to describe residential burglaries diffusion, employing Lévy flights dynamics. A continuous model is presented, introducing bidimensional fractional operator diffusion and its differences with the 1-dimensional case. Our results show, graphically, the hotspot's existence solution in a 2-dimensional attractiveness field, even fractional derivative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As a result, different types of heat conduction equations have emerged and this has led to the development of non-classical theories on heat conduction. In this sense, fractional operators with singular or non-singular kernels have played a significant role in various types of real-world problems [1][2][3][4][5][6]. For instance, in a thin rectangular plate the non-local relation between the heat flux q (t) and the temperature gradient gradT = ∂T ∂x ∂T ∂y can be given by [7] q (t) = −k t 0 K (t − τ) gradT (x, y, τ) dτ,…”
Section: Introductionmentioning
confidence: 99%
“…As a result, different types of heat conduction equations have emerged and this has led to the development of non-classical theories on heat conduction. In this sense, fractional operators with singular or non-singular kernels have played a significant role in various types of real-world problems [1][2][3][4][5][6]. For instance, in a thin rectangular plate the non-local relation between the heat flux q (t) and the temperature gradient gradT = ∂T ∂x ∂T ∂y can be given by [7] q (t) = −k t 0 K (t − τ) gradT (x, y, τ) dτ,…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that MHD and Rayleigh number influence the flow behavior. By assessing the literature papers [50][51][52][53][54][55][56][57], it has been found that convection and finite element methods are described.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical modeling can be used in many areas such as medicine [5,6], economic [7], environment [8], transport [9], and finance [10,11]. We note that, for each area, there have been a number of prominent illustrative modeling applications that were proposed and developed in recent years, especially modeling infectious epidemics [12], urban crim [13], pricing of different types of options [14], chaotic systems [15], non linear evolution dynamics [16], etc. In the field of financial applications, and to the best of to our knowledge, there are only five references, namely refs.…”
Section: Introductionmentioning
confidence: 99%